Analyzing the Electronic Coupling in Molecular Crystals—The Instructive Case of α‐Quinacridone. Issue 5 (28th March 2019) - Winkler, Christian; Mayer, Florian; Zojer, Egbert
Abstract: In the present article, an evaluation of different approaches for estimating the electronic coupling and charge‐transport parameters in organic semiconductors is provided. As a testbed for that comparison, the α‐polymorph of quinacridone is chosen. This system is particularly well suited for the purpose, as α‐quinacridone intermolecular interactions in distinct crystallographic directions are dominated by the three mechanisms most relevant in organic semiconductors: π‐stacking, H‐bonding, and van der Waals stacking. Density‐functional theory‐based simulations yield a comparably complex band structure, which provides the means for demonstrating shortcomings of commonly applied approaches. These include the estimation of transport properties based on bandwidths and the calculation of electronic transfer integrals considering molecular dimers. As a particularly promising alternative, the fitting of suitably complex tight‐binding models to the DFT‐calculated bands in the entire Brillouin zone is proposed. These fits bear the advantage of directly producing intermolecular coupling constants for all relevant neighboring molecules as input parameters for hopping and dynamic disorder models. They also yield an analytic expression for the electronic bands. These allow the extraction of parameters relevant for band‐transport models (like group velocities and effective masses) in the entire Brillouin zone. Abstract : Different computational approaches for describing charge‐transport parameters in organic semiconductor crystals are evaluated using the α‐polymorph of quinacridone as a prototypical example. A rather complex tight‐binding model is fitted to the electronic band structure. Using this model, it is possible to obtain intermolecular electronic couplings and effective masses and to decompose electronic bands into individual contributions.